Essential facets of competence that enable trust in medical graduates: a ranking study among physician educators in two countries - Wijnen-Meijer, Marjo (Bohn Stafleu van Loghum, 2013)
One way to operationalize the assessment of trainees in a competency-based context is to determine whether they can be entrusted with critical activities. To determine which facets of competence (FOCs) are most informative for such decisions, we performed a Delphi study among Dutch educators. In the current study, the resulting list of facets of competence was evaluated among experienced Dutch and German clinical educators to determine which facets appear most relevant and to evaluate the agreement among experts in different countries as a support for their external validity. Eight Dutch and eight German experts scored each FOC on a five-point scale for relevance. A rank-order comparison showed that there was almost full agreement about the top 10 FOCs, among which ‘Scientific and empirical grounded method of working’, ‘Knowing and maintaining own personal bounds and possibilities’, ‘Active professional development’, ‘Teamwork and collegiality’, ‘Active listening to patients’, and ‘Verbal communication with colleagues and supervisors’. We conclude that these facets of competence may be used in a training for educators who need to make entrustment decisions about trainees.